Quality of life and job satisfaction of nurses - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2003)
The purpose of this study was to determine whether there is a relation between job satisfaction and quality of life (QOL) of nurses. The study was based on a sample of 501 nurses. job satisfaction was measured by means of the Short Form Minnesota Questionnaire and QOL by means of WHOQOL-BRIEF. The results demostrated a positive correlation between job satisfaction and QOL. It was also found that job satisfaction and QOL scores of nurses showed a significant difference according to their age, economic level, marital status, duration of working life, and position at work.
Keywords: job satisfaction; quality of life; work condition